A novel agent attenuates cardiotoxicity and improves antitumor activity of doxorubicin in breast cancer cells. Issue 4 (10th October 2018) - Zhang, Ying; Deng, Hongkuan; Zhou, Hefeng; Lu, Yucong; Shan, Luchen; Lee, Simon Ming‐Yuen; Cui, Guozhen
Abstract: Doxorubicin (Dox) is a well‐known chemotherapeutic agent used in the treatment of various cancers. However, Dox‐induced cardiotoxicity limits its further clinical use. We have previously reported a small molecular named biotin‐conjugated ADTM analog (BAA) that exhibits cytoprotective effects against oxidative stress–induced cell injury in cardiomyoblast H9c2 cells. Here, the protective effects of BAA, indexed by attenuation of the cardiotoxicity induced by Dox as well as synergistic antitumor activity that increases the chemotherapeutic efficacy of Dox were investigated. Our results demonstrated that BAA significantly ameliorated Dox‐induced toxicity in the H9c2 cells and zebrafish models. In addition, BAA attenuated Dox‐induced endoplasmic reticulum (ER) stress in H9c2 cells. An ER stress inhibitor, 4‐phenylbutyric acid, reversed the protective effect of BAA in H9c2 cells. In contrast, in human breast tumor MDA‐MB‐231 cells, BAA significantly enhanced Dox‐induced cytotoxicity through upregulating Dox‐induced ER stress response. Taken together, our findings indicate that Dox combined with BAA can significantly enhance its antitumor activity in breast cancer cells and reduce its cardiotoxicity, at least in part, by mediating ER stress activation. Abstract : 1. Biotin‐conjugated ADTM analog (BAA) attenuated doxorubicin (Dox)‐induced cardiotoxicity in cardiomyoblast H9c2 cells and zebrafish. 2. BAA enhanced the antitumor activity of Dox in breast cancer cells MDA‐MB‐231. 3. Endoplasmic reticulum (ER) stress inhibitor 4‐phenylbutyric acid blunted the actions of BAA combined with Dox in the different cells. ER stress response is involved in the mechanisms of the actions.